Calcium signaling and mitochondrial function - Nicholls, David (Henry Stewart Talks, 2007)
The calcium uniporter, Mitochondrial calcium efflux pathways, Steady state and net uptake, The regulation of cytoplasmic calcium by mitochondria, The role of phosphate and the matrix calcium phosphate complex, Uniporter kinetics, The set-point concept, Matrix dehydrogenase regulation by calcium, The permeability transition
Archived at 2018/05/31